Tumor ablation by intratumoral Ra-224-loaded wires induces anti-tumor immunity against experimental metastatic tumors - Confino, Hila; Umansky, Viktor (Cancer immunology immunotherapy, 2015)
The current systemic anti-metastatic treatment is chemotherapy. Chemotherapy reacts mostly against replicating cells, which makes this therapy not specific. Moreover, resting cancer cells will not be destroyed. A better alternative is an engagement of the host immune system to react against tumor-associated antigens. An efficient immune-stimulating technique is an ablation of the tumor that results in the release of tumor antigens. Our ablation strategy is an innovative alpha-radiation-based technology, diffusing alpha-emitters radiation therapy (DaRT), which efficiently destroys local tumors and provides thereby an antigenic supply for antigen-presenting cells to stimulate T cells. Mice bearing weakly immunogenic DA3 adenocarcinoma or highly immunogenic CT26 colon carcinoma were treated by DaRT. Anti-tumor immune responses following tumor destruction were evaluated by (1) the resistance to a tumor challenge; (2) scanning by a CT imaging device for elimination of lung metastases; (3) improved tumor control when combining DaRT with an immunoadjuvant (CpG). CT26 model: 63–77 % of DaRT-treated mice became resistant to a re-inoculated tumor compared to 29–33 % resistant mice in the control. DA3 model: (1) The growth rate of challenge tumors was the lowest in mice which their primary tumor was treated by DaRT. (2) Most (93 %) mice in the control group developed lung metastases compared to 56 % in the DaRT group. (3) Combining DaRT with CpG resulted in a better control of the primary tumor. Our study offers a technique to eliminate local and distant malignant cells, regardless of their replication status, by stimulating specific anti-tumor immunity through the supply of tumor antigens from the destroyed tumor.